2008
DOI: 10.1007/bf03405466
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Promotions at Point-of-sale

Abstract: Objectives:The retail environment provides important opportunities for tobacco industry communication with current, former, and potential smokers. This study documented the extent of tobacco promotions at the retail point-of-sale and examined associations between the extent of tobacco promotions and relevant city and store characteristics. Methods:In each of 20 Ontario cities, 24 establishments were randomly selected from lists of convenience stores, gas stations, and grocery stores. Trained observers captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 15 publications
3
46
0
Order By: Relevance
“…In addition to small sample sizes, possible differences in unplanned purchase rates between our study and Carter et al could stem from differences in disposable income or level of nicotine addiction among purchasers. The percentage of unplanned cigarette purchases could also be lower because studies have shown that grocery stores have a lower concentration of tobacco POS advertising than other store types, such as convenience stores 13. In addition, not all checkout lanes at the grocery stores sold cigarettes, therefore not all individuals visiting the store would be exposed to tobacco displays and advertising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to small sample sizes, possible differences in unplanned purchase rates between our study and Carter et al could stem from differences in disposable income or level of nicotine addiction among purchasers. The percentage of unplanned cigarette purchases could also be lower because studies have shown that grocery stores have a lower concentration of tobacco POS advertising than other store types, such as convenience stores 13. In addition, not all checkout lanes at the grocery stores sold cigarettes, therefore not all individuals visiting the store would be exposed to tobacco displays and advertising.…”
Section: Discussionmentioning
confidence: 99%
“…We did not measure the quantity of advertising in the stores in this study. Studies from California, Ontario, Massachusetts, Guatemala, Argentina and Ireland indicate that the quantity of tobacco POS advertising and displays vary greatly by store type, proximity to schools and neighbourhood socioeconomic status 13 19 21. In addition, sampling primarily occurred during weekdays, and only limited survey collection was performed on weekends, which could result in an oversampling of unemployed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia retailers receive more money for displaying tobacco than they do for other types of product 12. North American studies have also found significantly more PoS tobacco promotions near schools and in low-income and minority neighbourhoods than in better educated, higher-income, predominantly white neighbourhoods 13 14…”
Section: Introductionmentioning
confidence: 99%
“…The borders were drawn arbitrarily to form a ∼1.19 km 2 area that includes the University of Buenos Aires Hospital. The checklist used in this study assesses characteristics of tobacco PoS advertising and is identical to that used in previous studies 6 7. The percentage of missing data for each variable ranged from 0% to 16%, and an available case-analysis was used to analyse the results.…”
Section: Methodsmentioning
confidence: 99%